A three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector and a preparation method thereof
Patent Information
- Application Number
- CN202310705741.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-06-14
AI Technical Summary
该过程繁琐复杂,难以自动化,良品率低
[0038](1)借助于射频磁控溅射工艺,在衬底上沉积一层透明的非晶铟镓锌氧化物薄膜。通过适当的退火工艺完成上述样品的退火后,借助热蒸发镀膜机与掩膜板完成图案化。借助固相配体交换工艺,在图案化的衬底上沉积一层碘封端的硫化铅量子点薄膜(PbS-TBAI)。随即,继续旋涂一层基于液相配体交换工艺的碘封端硫化铅量子点薄膜(PbS-I)完成三层硫化铅/氧化铟镓锌异质结光电导型近红外光电探测器的制备。与传统的仅基于固相配体交换工艺的器件相比,本发明通过进一步地沉积基于液相配体交换的硫化铅量子点薄膜(PbS-I)。将液相配体交换工艺与固相配体交换工艺的优点相结合,构建了三层异质结,提升了器件的比探测率、光响应度、响应速度及空气稳定性等探测性能。
Smart Images

Figure CN116632098B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor technology and relates to a three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector and its fabrication method. Background Technology
[0002] In the era of the Internet of Things (IoT), near-infrared photodetectors are widely used in near-infrared imaging, autonomous driving, industrial automation, safety and environmental monitoring, and spectroscopy. Currently, commercially available infrared photodetectors mostly use traditional semiconductor materials such as InGaAs and HgCgTe as the photosensitive layer. These materials are expensive, their fabrication process relies on high-temperature and high-vacuum processes, and they have high requirements for substrate and crystallinity, and cannot be integrated with flexible electronics. These issues result in high production costs and equipment investment, hindering the wider application of infrared photodetectors. With the rapid development of quantum dots, perovskite, and other nanomaterials of photosensitive semiconductors, quantum dot-based near-infrared photodetectors have attracted widespread attention as a reliable candidate material for low-cost near-infrared photodetectors.
[0003] As a zero-dimensional nanomaterial, quantum dots exhibit quantum confinement effects, and their band gap can be tuned with the quantum dot size. Quantum dots can be prepared via solution methods and deposited using processes such as spin coating, blade coating, and spray coating, offering advantages such as low raw material cost, simple fabrication processes, and low equipment investment. Furthermore, quantum dots possess high absorption coefficients; even nanoscale quantum dot films can absorb incident light, thus making them suitable for flexible devices. Currently, the application of quantum dots in photoelectric detection is mainly limited by the relatively low carrier mobility and high defect state concentration of quantum dot films. The former limits the photoresponsivity and specific detectivity of quantum dot-based devices, while the latter limits their response speed.
[0004] By constructing a lead sulfide quantum dot thin film / amorphous indium gallium zinc oxide (IGaZn) heterojunction, the drawback of low specific detectivity and photoresponsivity caused by the low carrier mobility of quantum dot thin films is overcome. In this heterojunction, the lead sulfide quantum dot layer is responsible for absorbing incident light and generating photogenerated carriers. After the photogenerated carriers diffuse to the heterojunction interface, they separate; photogenerated electrons are injected into the amorphous IGaZn layer, while photogenerated holes remain in the lead sulfide quantum dot layer. Under the action of a bias voltage, the photogenerated electrons pass through the high carrier mobility of the amorphous IGaZn layer to participate in the circulation of the external circuit. Before recombination with photogenerated holes, the photoconductivity gain is significantly improved, thereby enhancing the specific detectivity and photoresponsivity of the device.
[0005] Currently reported device structures involve heterojunctions formed by solid-state ligand exchange-based lead sulfide quantum dot films and amorphous indium gallium zinc oxide films. Lead sulfide quantum dots synthesized via hot-injection polymerization contain long-chain oleic acid ligands, which hinder carrier transport between quantum dots. Therefore, ligand exchange processes are typically used to replace the long-chain ligands with short-chain ligands. Solid-state ligand exchange is a traditional ligand exchange process. Ligand exchange is achieved by spin-coating oleic acid-terminated quantum dot ink into a film and then covering it with a short-chain ligand solution. Devices based on this process have the following drawbacks:
[0006] 1. To ensure complete ligand exchange, solid-phase ligand exchange processes are limited to films smaller than 10 nanometers. Therefore, the above steps must be repeated, spin-coating layer by layer to obtain a sufficiently thick film. This process is tedious, complex, difficult to automate, and results in low yield. Furthermore, the vast majority of quantum dot ink and solvent are wasted during spin-coating.
[0007] 2. In solid-phase ligand exchange, the quantum dot film inevitably breaks down, resulting in a decrease in the quality of the quantum dot film, a reduction in carrier mobility, and consequently, a lower specific detectivity and photoresponsivity of the device.
[0008] 3. Lead sulfide quantum dot films based on solid-phase ligand exchange are easily oxidized when exposed to air, which reduces the air stability of the device.
[0009] Considering the above issues, the emerging liquid-phase ligand exchange process has attracted attention. In this process, quantum dots are dissolved in a solvent before film formation, and ligand exchange occurs between the liquid phases. The ligand-exchanged lead sulfide quantum dots can be directly dissolved in a solvent to prepare quantum dot ink, which can then be directly deposited using spin-coating. Compared to solid-phase ligand exchange, liquid-phase ligand exchange significantly simplifies the process, improves the reproducibility of device fabrication, avoids waste of quantum dot ink and solvent, and is more suitable for automated industrial production. Furthermore, the concentration of the quantum dot ink prepared by liquid-phase ligand exchange can be directly controlled to regulate the thickness of the quantum dot film. The prepared quantum dot films have smooth surface morphology and good electrical properties and air stability. The fabricated devices exhibit superior specific detectivity and photoresponsivity. Currently, lead sulfide quantum dot films based on liquid-phase ligand exchange have not yet been applied to photoconductive photodetectors. However, devices based on liquid-phase ligand exchange technology also have their inherent drawbacks. Due to the higher defect state density, these devices based on liquid-phase ligand exchange technology have a slower response speed than those based on solid-phase ligand exchange technology. Summary of the Invention
[0010] To overcome the shortcomings of the prior art, the present invention aims to provide a three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector and its fabrication method, which enables the device to have higher specific detectivity and photoresponsivity, better air stability and faster response speed, and a simpler fabrication process and lower production cost.
[0011] To achieve the above objectives, this application adopts the following technical solution:
[0012] A three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector comprises, from bottom to top, a substrate, an amorphous indium gallium zinc oxide thin film prepared by radio frequency magnetron sputtering, a patterned aluminum electrode, an iodine-terminated lead sulfide quantum dot film (PbS-TABI) prepared by solid-phase ligand exchange process, and an iodine-terminated lead sulfide quantum dot film (PbS-I) prepared by liquid-phase ligand exchange process.
[0013] Furthermore, the total thickness of the iodine-terminated lead sulfide quantum dot film (PbS-TABI) prepared based on the solid-phase ligand exchange process and the iodine-terminated lead sulfide quantum dot film (PbS-I) prepared based on the liquid-phase ligand exchange process is 40-320 nanometers.
[0014] Furthermore, the thickness of the iodine-terminated lead sulfide quantum dot film (PbS-TABI) prepared based on the solid-phase ligand exchange process is 10-20 nanometers.
[0015] Furthermore, the thickness of the iodine-terminated lead sulfide quantum dot film (PbS-I) prepared based on the liquid-phase ligand exchange process is 30-300 nanometers.
[0016] Furthermore, in the amorphous indium gallium zinc oxide target used for the radio frequency magnetron sputtering preparation of amorphous indium gallium zinc oxide thin films, the ratio of indium, gallium, and zinc elements is 1:1:1, the working pressure is 0.37 Pa, the power is 60 W, and the sputtering time is 5 minutes.
[0017] Furthermore, the substrate is a white glass substrate, a flexible plastic substrate, or a paper substrate.
[0018] The fabrication method of a three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector includes the following steps:
[0019] Step 1: An amorphous indium gallium zinc oxide thin film is deposited on a clean and dry substrate using an RF magnetron sputtering process; after annealing, the thin film is used to pattern aluminum electrodes using a mask and thermal evaporation deposition technology.
[0020] Step 2: Using spin coating technology, a thin film of iodine-terminated lead sulfide quantum dots is deposited on the sample obtained in Step 1 using a solid-phase ligand exchange process.
[0021] Step 3: Using spin coating technology, iodine-terminated lead sulfide quantum dot ink prepared by liquid phase ligand exchange process is deposited on the sample obtained in step 2 to obtain a three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector.
[0022] Furthermore, step 2 specifically includes:
[0023] Step 2.1: Dissolve 2 mmol of lead oxide in a mixture of 10 mL of octadecene and 1.5 mL of oleic acid, and evacuate the mixture to a vacuum using a Schlenk linear reaction system. Gradually raise the temperature to 95°C and maintain this temperature until the turbid lead oxide solution transforms into a clear lead precursor solution. Use an inert gas to repeatedly wash the lead precursor solution with an inert gas using a Schlenk linear reaction system to ensure it is dry and oxygen-free. In an inert gas environment, raise the temperature of the lead precursor solution to 120°C, and rapidly inject 10 mL of a 0.2 mol / L solution of hexamethyldisilazane in octadecene into the reaction system. Then immediately cool the reaction system to 35°C using an ice-water bath.
[0024] Step 2.2: The reaction was completely stopped by injecting 25 mL of acetone into the reaction product of Step 2.1, and 20 mL of methanol was added to separate the reaction system into layers and remove the supernatant. Excess acetone was added to precipitate the reaction product, the supernatant was removed, and toluene was added to dissolve the precipitate. The above steps were repeated three times to obtain a solid product, which was dried under vacuum overnight to obtain oleic acid-terminated lead sulfide quantum dots.
[0025] Step 2.3: Dissolve the oleic acid-terminated lead sulfide quantum dots obtained in step 2.2 in n-octane solution to obtain oleic acid-terminated quantum dot ink with a concentration of 5-50 mg / mL;
[0026] Step 2.4: Using spin coating technology, spin coat the oleic acid-terminated quantum dot ink onto the substrate at a speed of 3000 rpm for 20 seconds.
[0027] Step 2.5: Then, cover the sample with a methanol solution of 10 mg / mL tetrabutylammonium iodide for 60 seconds to complete the ligand exchange between the solid and liquid phases; then, using spin coating technology, spin the liquid away from the sample at a speed of 3000 rpm.
[0028] Step 2.6: Cover the sample with methanol solution and spin-coate the sample at a speed of 3000 rpm. Repeat step 2.6 twice to wash away oleic acid and excess tetrabutylammonium iodide to obtain a PbS-TBAI film.
[0029] Step 2.7, repeat steps 2.4-2.6 one to three times to obtain a sufficiently thick PbS-TBAI film;
[0030] The samples obtained in steps 2.8 and 2.6 are either not annealed or annealed in air at 50°C to 150°C for 10 minutes.
[0031] Furthermore, step 3 specifically includes:
[0032] Step 3.1: Dissolve 2 mmol of lead oxide in a mixture of 10 mL of octadecene and 1.5 mL of oleic acid, and evacuate the mixture to a vacuum using a Schlenk linear reaction system. Gradually raise the temperature to 95°C and maintain this temperature until the turbid lead oxide solution transforms into a clear lead precursor solution. Use an inert gas to repeatedly wash the lead precursor solution with an inert gas using a Schlenk linear reaction system to ensure it is dry and oxygen-free. In an inert gas environment, raise the temperature of the lead precursor solution to 120°C, and rapidly inject 10 mL of a 0.2 mol / L solution of hexamethyldisilazane in octadecene into the reaction system. Then immediately cool the reaction system to 35°C using an ice-water bath.
[0033] Step 3.2: The reaction was completely stopped by injecting 25 mL of acetone into the reaction product of step 3.1, and 20 mL of methanol was added to separate the reaction system into layers and remove the supernatant; excess acetone was added to precipitate the reaction product, the supernatant was removed, and toluene was added to dissolve the precipitate; the above steps were repeated three times to obtain a solid product, which was vacuum dried overnight to obtain oleic acid-terminated lead sulfide quantum dots.
[0034] Step 3.3: Dissolve the oleic acid-terminated lead sulfide quantum dots in n-hexane to obtain a n-hexane solution of oleic acid-terminated quantum dots with a concentration of 10 mg / mL;
[0035] Step 3.4: Mix the above-mentioned hexane solution of quantum dots with an equal volume of N,N-dimethylformamide solution of lead iodide and ammonium acetate, wherein the concentration of lead iodide is 0.1 mol / L and the concentration of ammonium acetate is 0.04 mol / L; stir the mixture vigorously until it separates into layers, and remove the supernatant; wash the black quantum dot solution with hexane, add 10 mL of toluene and centrifuge to allow the quantum dots to precipitate, remove the supernatant and vacuum dry for ten minutes to obtain iodine-terminated quantum dot powder;
[0036] Step 3.5: Dissolve iodine-capped quantum dot powder at a concentration of 50-200 mg / mL in a mixed solution of butylamine, pentamine, and hexylamine with a volume ratio of 10:3:2, and spin-coat an iodine-capped lead sulfide quantum dot film (PbS-I) at a speed of 2500 rpm for 60 seconds.
[0037] Compared with the prior art, the advantages of the present invention are:
[0038] (1) A transparent amorphous indium gallium zinc oxide (IGaZO) thin film is deposited on a substrate using radio frequency magnetron sputtering. After annealing the sample using an appropriate annealing process, patterning is performed using a thermal evaporation coating machine and a mask. An iodine-terminated lead sulfide quantum dot (PbS-TBAI) thin film is deposited on the patterned substrate using a solid-state ligand exchange process. Subsequently, an iodine-terminated lead sulfide quantum dot (PbS-I) thin film based on a liquid-state ligand exchange process is spin-coated to complete the fabrication of a three-layer lead sulfide / IGaZO heterojunction photoconductive near-infrared photodetector. Compared with traditional devices based solely on solid-state ligand exchange processes, this invention further deposits a lead sulfide quantum dot (PbS-I) thin film based on liquid-state ligand exchange. By combining the advantages of liquid-state ligand exchange and solid-state ligand exchange processes, a three-layer heterojunction is constructed, improving the detection performance of the device, such as specific detectivity, photoresponsivity, response speed, and air stability.
[0039] (2) Devices based solely on liquid-phase ligand exchange technology have not been reported. However, compared to these, this invention constructs a three-layer heterojunction by introducing a solid-phase ligand exchange-based quantum dot film (PbS-TBAI) between a lead sulfide quantum dot film (PbS-I) based on liquid-phase ligand exchange and an amorphous indium gallium zinc oxide film (a-IGZO). This improves the device's response speed and maintains high levels of specific detectivity, photoresponsivity, and response speed. In this invention, the solid-phase ligand exchange-based quantum dot film (PbS-TABI), with its lower defect state concentration, acts as a passivation layer, providing "layer passivation" and maintaining high levels of air stability. Its contact with the amorphous indium gallium zinc oxide allows for rapid separation of photogenerated carriers at the heterojunction interface, ensuring the device's high response speed.
[0040] Table 1 shows a comparison of the detection performance of this invention with that of solid-phase ligand exchange devices and liquid-phase ligand exchange devices.
[0041] Table 1. Comparison of detection performance of the present invention with those based solely on solid-phase ligand exchange devices and those based solely on liquid-phase ligand exchange devices.
[0042]
[0043] (3) In this invention, the absorption of incident light is mainly achieved by a quantum dot film (PbS-I) based on liquid-phase ligand exchange. The number of spin-coating steps for the quantum dot film based on solid-phase ligand exchange can be controlled to three or less. The lead sulfide quantum dot film based on liquid-phase ligand exchange can directly obtain a high-quality film with a thickness of more than 100 nanometers by adjusting the concentration of the precursor solution, thereby achieving sufficient absorption of incident light. This avoids the problems of complex operation, poor repeatability, deterioration of quantum dot film quality, and solvent waste caused by excessive spin-coating steps in the solid-phase ligand exchange process.
[0044] PbS-TBAI films based on solid-phase ligand exchange serve as passivation agents, optimizing carrier transport between heterojunctions. Their thickness is typically 10-20 nanometers. Experiments have shown that PbS-TBAI films exceeding 20 nanometers suffer from increased processing complexity, lower yield, and more defects. PbS-I films based on liquid-phase ligand exchange primarily function as incident light absorbers. Their thickness should not be less than 30 nanometers or too thick, ideally controlled between 30-300 nanometers to ensure adequate absorption. A thickness exceeding 300 nanometers leads to wasted quantum dot ink, decreased film quality, and increased dark current. Attached Figure Description
[0045] Figure 1 This is a schematic diagram of the device structure of the present invention;
[0046] Figure 2 The images show typical dark-state current-voltage curves and near-infrared light irradiation current-voltage curves of the infrared photodetector prepared in Example 1.
[0047] Figure 3 The graph shows the specific detectivity and photoresponsivity of the infrared photodetector prepared in Example 1 under near-infrared light illumination as a function of incident light power.
[0048] Figure 4 The transient response curve of the infrared photodetector prepared in Example 1 is shown.
[0049] Figure 5 The graph shows the response speed of the infrared photodetector prepared in Example 1 as a function of incident light power.
[0050] Figure 6 The typical dark-state current-voltage curves and near-infrared light irradiation current-voltage curves of the bilayer heterojunction device based on solid-phase ligand exchange technology compared to the trilayer heterojunction device designed in this invention.
[0051] Figure 7 The graphs show the typical specific detectivity and photoresponsivity as a function of incident light power for a bilayer heterojunction device based solely on solid-phase ligand exchange and a trilayer heterojunction device designed in this invention.
[0052] Figure 8 The transient response curves of the bilayer heterojunction device based solely on liquid-phase ligand exchange are compared to the three-layer heterojunction device designed in this invention.
[0053] Figure 9 The graph shows the specific detectivity and photoresponsivity of a bilayer heterojunction device based solely on liquid-phase ligand exchange as a function of incident light power. Detailed Implementation
[0054] The technical solutions in the embodiments of the present invention will be clearly and completely described below.
[0055] The present invention relates to a method for fabricating a three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector:
[0056] Lead sulfide colloidal quantum dots were prepared using a Schlenk line synthesis apparatus and a hot-injection process. The quantum dots were cleaned using the polarity of an organic solvent, and then vacuum-dried to obtain oleic acid-terminated quantum dot powder. The quantum dot powder was dissolved in a low concentration of n-hexane and mixed with a solution of lead iodide and ammonium acetate in N,N-dimethylformamide, and vigorously shaken until phase transfer occurred. The n-hexane supernatant was removed, and the black quantum dot solution was repeatedly washed with n-hexane. Toluene was added, stirred, and centrifuged to allow the iodine-terminated quantum dots to settle. The supernatant was removed, and the mixture was vacuum-dried to obtain iodine-terminated quantum dot powder. This process is known as the liquid-phase ligand exchange process. An amorphous indium gallium zinc oxide transparent semiconductor film of a certain thickness was deposited on a substrate using radio frequency magnetron sputtering. After annealing, patterning was completed using a mask and thermal evaporation. A thin film of oleic acid-terminated lead sulfide quantum dots was deposited on a patterned sample using a spin coater. This was followed by covering the film with a methanol solution of tetrabutylammonium iodide for 60 seconds, followed by spin-coating. This process of covering with methanol solution and spin-coating was repeated to obtain a PbS-TBAI film based on a solid-phase ligand exchange process. This process was repeated multiple times to obtain a sufficiently thick PbS-TBAI film. Finally, iodine-terminated quantum dot ink based on a liquid-phase ligand exchange process was spin-coated onto the sample using a spin coater to obtain a final film. Figure 1 The diagram shows a three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector.
[0057] A method for fabricating a three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector includes the following steps:
[0058] 1) Transfer 10 mL of octadecene, 1.5 mL of oleic acid, and 0.446 g of yellow lead oxide to the reaction system. Using a Schlenk linear synthesis system, evacuate the reaction system to a vacuum and stir. After the reaction system is free of bubbles, heat to 95°C until the yellow lead oxide is completely dissolved and the octadecene solution of yellow lead oxide becomes clear and transparent. This process takes approximately 2 hours or more. Clean the reaction system by purging nitrogen gas and then evacuating it to completely isolate it from water and oxygen. After the reaction system reaches 120°C, quickly inject 10 mL of an octadecene solution containing 210 μL of hexamethyldisilazane. Immediately cool the reaction system to room temperature in a cold water bath.
[0059] 2) Add sufficient methanol (approximately 10 mL) to the black solution obtained in step 1) until it separates into layers, and remove the supernatant containing oleic acid. Add excess acetone (approximately 100 mL) to the lower layer of black solution containing quantum dots until the quantum dots settle, and centrifuge to remove the supernatant. Add a small amount of toluene (approximately 1 mL) to dissolve the quantum dots. Repeat the above process three times to wash the quantum dots and remove excess oleic acid ligands. Vacuum dry to obtain oleic acid-terminated lead sulfide quantum dot powder.
[0060] 3) Dissolve the small-sized quantum dot powder obtained in step 2) in n-hexane at a concentration of 10 mg / mL, and mix it with an equal volume of an N,N-dimethylformamide solution of lead iodide and ammonium acetate. The concentration of lead iodide is 0.1 mol / L, and the concentration of ammonium acetate is 0.04 mol / L. Stir the mixture vigorously until it separates into layers, and remove the supernatant. Wash the black quantum dot solution by adding and removing n-hexane. Repeat this washing step three times. Add 10 mL of toluene and centrifuge to allow the quantum dots to settle. Remove the supernatant and vacuum dry for ten minutes to obtain iodine-terminated quantum dot powder. This step is the liquid-phase ligand exchange process.
[0061] 4) Select a white glass, flexible plastic, or paper substrate and deposit amorphous indium gallium zinc oxide transparent thin films using radio frequency magnetron sputtering technology. During RF magnetron sputtering, the working pressure is 0.37 Pa, the power is 60 W, and the time is 5 minutes. After sputtering, the sample is annealed on a 400℃ hot plate for 1 hour. Patterning is then performed using a mask and a thermal evaporation coating machine. The metal used for thermal evaporation is aluminum. If a flexible plastic or paper substrate is selected, the annealing process is omitted, and patterning is directly performed using a mask and a thermal evaporation coating machine after sputtering.
[0062] 5) Dissolve oleic acid-terminated lead sulfide quantum dots in n-octane solution at a concentration of 5 mg / mL-50 mg / mL to obtain oleic acid-terminated quantum dot ink.
[0063] 6) Using spin coating technology, the oleic acid-terminated quantum dot ink is spin-coated onto the substrate at a speed of 3000 rpm for 20 seconds.
[0064] 7) Then cover the sample with a methanol solution of 10 mg / mL tetrabutylammonium iodide for 60 seconds to complete the ligand exchange between the solid and liquid phases; use spin coating technology to spin the liquid away from the sample at a speed of 3000 rpm.
[0065] 8) Cover the sample with methanol solution and spin-coate the sample at 3000 rpm; repeat step 8) twice to wash away oleic acid and excess tetrabutylammonium iodide.
[0066] 9) Repeat steps 6) to 8) one to three times to obtain a sufficiently thick PbS-TBAI layer.
[0067] 10) The sample obtained in step 9) is annealed in air at 100°C for 10 minutes.
[0068] 11) Dissolve the iodine-terminated quantum dots obtained in step 3) at a concentration of 50 mg / mL-200 mg / mL in a mixed solution of butylamine, pentamine, and hexylamine at a volume ratio of 10:3:2, filter, and obtain iodine-terminated lead sulfide quantum dot ink. Drop-coat this ink onto the sample obtained in step 10), and spin-coat it at 2500 rpm for 60 seconds to obtain a three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector.
[0069] The following are some specific examples.
[0070] Example 1:
[0071] 1) Transfer 10 mL of octadecene, 1.5 mL of oleic acid, and 0.446 g of yellow lead oxide to the reaction system. Using a Schlenk linear synthesis system, evacuate the reaction system to a vacuum and stir. After the reaction system is free of bubbles, heat to 95°C until the yellow lead oxide is completely dissolved and the octadecene solution of yellow lead oxide becomes clear and transparent. This process takes approximately 2 hours or more. Clean the reaction system by purging nitrogen gas and then evacuating it to completely isolate it from water and oxygen. After the reaction system reaches 120°C, quickly inject 10 mL of an octadecene solution containing 210 μL of hexamethyldisilazane. Immediately cool the reaction system to room temperature in a cold water bath.
[0072] 2) Add sufficient methanol (approximately 10 mL) to the black solution obtained in step 1) until it separates into layers, and remove the supernatant containing oleic acid. Add excess acetone (approximately 100 mL) to the lower layer of black solution containing quantum dots until the quantum dots settle, and centrifuge to remove the supernatant. Add a small amount of toluene (approximately 1 mL) to dissolve the quantum dots. Repeat the above process three times to wash the quantum dots and remove excess oleic acid ligands. Vacuum dry to obtain oleic acid-terminated lead sulfide quantum dot powder.
[0073] 3) Dissolve the small-sized quantum dot powder obtained in step 2) in n-hexane at a concentration of 10 mg / mL, and mix it with an equal volume of an N,N-dimethylformamide solution of lead iodide and ammonium acetate. The concentration of lead iodide is 0.1 mol / L, and the concentration of ammonium acetate is 0.04 mol / L. Stir the mixture vigorously until it separates into layers, and remove the supernatant. Wash the black quantum dot solution by adding and removing n-hexane. Repeat this washing step three times. Add 10 mL of toluene and centrifuge to allow the quantum dots to settle. Remove the supernatant and vacuum dry for ten minutes to obtain iodine-terminated quantum dot powder. This step is the liquid-phase ligand exchange process.
[0074] 4) A clear glass substrate was selected, and an amorphous indium gallium zinc oxide transparent thin film was deposited using radio frequency magnetron sputtering technology. During the radio frequency magnetron sputtering process, the working pressure was 0.37 Pa, the power was 60 W, and the time was 5 minutes. After sputtering, the sample was annealed on a 400℃ hot plate for 1 hour. Patterning was then completed using a mask and a thermal evaporation coating machine. The metal used for thermal evaporation was aluminum.
[0075] 5) Dissolve oleic acid-terminated lead sulfide quantum dots in n-octane solution at a concentration of 50 mg / mL to obtain oleic acid-terminated quantum dot ink.
[0076] 6) Using spin coating technology, the oleic acid-terminated quantum dot ink is spin-coated onto the substrate at a speed of 3000 rpm for 20 seconds.
[0077] 7) Then cover the sample with a methanol solution of 10 mg / mL tetrabutylammonium iodide for 60 seconds to complete the ligand exchange between the solid and liquid phases; use spin coating technology to spin the liquid away from the sample at a speed of 3000 rpm.
[0078] 8) Cover the sample with methanol solution and spin-coate the sample at 3000 rpm; repeat step 8) twice to wash away oleic acid and excess tetrabutylammonium iodide.
[0079] 9) Repeat steps 6) through 8) once.
[0080] 10) The sample obtained in step 9) is annealed at 100°C for 10 minutes.
[0081] 11) Dissolve the iodine-terminated quantum dots obtained in step 3) at a concentration of 50 mg / mL in a mixed solution of butylamine, pentamine, and hexylamine at a volume ratio of 10:3:2, filter, and obtain iodine-terminated lead sulfide quantum dot ink. Drop-coat this ink onto the sample obtained in step 10), and spin-coat it at 2500 rpm for 60 seconds to obtain a three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector.
[0082] Figure 2 The figures show typical dark-state current-voltage curves and near-infrared light irradiation curves of the three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector prepared in Example 1. As can be seen from the figures, under near-infrared light irradiation of 1064 nm and 45.3 μW, the device exhibits a current-voltage ratio close to 10. -4 Photocurrent of amperes and below 10 -9 The device exhibits a dark current of over 4 × 10⁻⁶ amperes. By adjusting the gate voltage, the device can demonstrate a dark current exceeding 4 × 10⁻⁶ amperes. 5 The signal-to-noise ratio.
[0083] Figure 3 The graphs show the specific detectivity and photoresponsivity of the three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector prepared in Example 1 under near-infrared light illumination as a function of incident light power. It can be seen that the specific detectivity and photoresponsivity of the device increase as the incident light power decreases. In the low light intensity region, the device can achieve a specific detectivity exceeding 10. 13 Jones's specific detectivity is in the 1 ampere per watt range of optical responsivity.
[0084] Figure 4 The transient response curve of the three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector prepared in Example 1 is shown. The rise time is 3.5 ms and the fall time is 3.6 ms (the incident light power is 0.947 μW at this time).
[0085] Figure 5 The figures show the response speed of the three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector prepared in Example 1 as a function of incident light power (square curves), the response speed of the two-layer heterojunction device based on liquid-phase ligand exchange technology as a function of incident light power (circular curves), and the response speed of the two-layer heterojunction device based on solid-phase ligand exchange technology as a function of incident light power (triangular curves). It can be seen that compared with devices based solely on liquid-phase ligand exchange and devices based solely on solid-phase ligand exchange, the three-layer heterojunction device designed in this invention can effectively improve the response speed.
[0086] Comparative Example 1:
[0087] 1) Transfer 10 mL of octadecene, 1.5 mL of oleic acid, and 0.446 g of yellow lead oxide to the reaction system. Using a Schlenk linear synthesis system, evacuate the reaction system to a vacuum and stir. After the reaction system is free of bubbles, heat to 95°C until the yellow lead oxide is completely dissolved and the octadecene solution of yellow lead oxide becomes clear and transparent. This process takes approximately 2 hours or more. Clean the reaction system by purging nitrogen gas and then evacuating it to completely isolate it from water and oxygen. After the reaction system reaches 120°C, quickly inject 10 mL of an octadecene solution containing 210 μL of hexamethyldisilazane. Immediately cool the reaction system to room temperature in a cold water bath.
[0088] 2) Add sufficient methanol (approximately 10 mL) to the black solution obtained in step 1) until it separates into layers, and remove the supernatant containing oleic acid. Add excess acetone (approximately 100 mL) to the lower layer of black solution containing quantum dots until the quantum dots settle, and centrifuge to remove the supernatant. Add a small amount of toluene (approximately 1 mL) to dissolve the quantum dots. Repeat the above process three times to wash the quantum dots and remove excess oleic acid ligands. Vacuum dry to obtain oleic acid-terminated lead sulfide quantum dot powder.
[0089] 3) A white glass substrate was selected, and an amorphous indium gallium zinc oxide transparent thin film was deposited using radio frequency magnetron sputtering technology. During the radio frequency magnetron sputtering process, the working pressure was 0.37 Pa, the power was 60 W, and the time was 5 minutes. After sputtering, the sample was annealed on a 400℃ hot plate for 1 hour. Patterning was then completed using a mask and a thermal evaporation coating machine. The metal used for thermal evaporation was aluminum.
[0090] 4) Dissolve oleic acid-terminated lead sulfide quantum dots in n-octane solution at a concentration of 50 mg / mL to obtain oleic acid-terminated quantum dot ink.
[0091] 5) Using spin coating technology, the oleic acid-terminated quantum dot ink is spin-coated onto the substrate at a speed of 3000 rpm for 20 seconds.
[0092] 6) Then cover the sample with a methanol solution of 10 mg / mL tetrabutylammonium iodide for 60 seconds to complete the ligand exchange between the solid and liquid phases; use spin coating technology to spin the liquid away from the sample at a speed of 3000 rpm.
[0093] 7) Cover the sample with methanol solution and spin-coate the sample at 3000 rpm; repeat step 8) twice to wash away oleic acid and excess tetrabutylammonium iodide.
[0094] 8) Repeat steps 5) through 7) once.
[0095] 9) The sample obtained in step 8) is annealed at 100°C for 10 minutes to obtain a device based solely on solid-phase coordination exchange.
[0096] Figure 6 The typical dark-state current-voltage curves and near-infrared light irradiation current-voltage curves of the bilayer heterojunction device based on solid-state ligand exchange technology show a significant difference in photocurrent compared to the three-layer heterojunction device designed in this invention.
[0097] Figure 7 The curves showing the specific detectivity and photoresponsivity of a bilayer heterojunction device based on solid-state ligand exchange technology as a function of incident light power are shown. Compared with the three-layer heterojunction device designed in this invention, the specific detectivity and photoresponsivity are significantly different.
[0098] Comparative Example 2:
[0099] 1) Transfer 10 mL of octadecene, 1.5 mL of oleic acid, and 0.446 g of yellow lead oxide to the reaction system. Using a Schlenk linear synthesis system, evacuate the reaction system to a vacuum and stir. After the reaction system is free of bubbles, heat to 95°C until the yellow lead oxide is completely dissolved and the octadecene solution of yellow lead oxide becomes clear and transparent. This process takes approximately 2 hours or more. Clean the reaction system by purging nitrogen gas and then evacuating it to completely isolate it from water and oxygen. After the reaction system reaches 120°C, quickly inject 10 mL of an octadecene solution containing 210 μL of hexamethyldisilazane. Immediately cool the reaction system to room temperature in a cold water bath.
[0100] 2) Add sufficient methanol (approximately 10 mL) to the black solution obtained in step 1) until it separates into layers, and remove the supernatant containing oleic acid. Add excess acetone (approximately 100 mL) to the lower layer of black solution containing quantum dots until the quantum dots settle, and centrifuge to remove the supernatant. Add a small amount of toluene (approximately 1 mL) to dissolve the quantum dots. Repeat the above process three times to wash the quantum dots and remove excess oleic acid ligands. Vacuum dry to obtain oleic acid-terminated lead sulfide quantum dot powder.
[0101] 3) A white glass substrate was selected, and an amorphous indium gallium zinc oxide transparent thin film was deposited using radio frequency magnetron sputtering technology. During the radio frequency magnetron sputtering process, the working pressure was 0.37 Pa, the power was 60 W, and the time was 5 minutes. After sputtering, the sample was annealed on a 400℃ hot plate for 1 hour. Patterning was then completed using a mask and a thermal evaporation coating machine. The metal used for thermal evaporation was aluminum.
[0102] 4) Dissolve oleic acid-terminated lead sulfide quantum dots in n-octane solution at a concentration of 50 mg / mL to obtain oleic acid-terminated quantum dot ink.
[0103] 5) Using spin coating technology, the oleic acid-terminated quantum dot ink is spin-coated onto the substrate at a speed of 3000 rpm for 20 seconds.
[0104] 6) Then cover the sample with a methanol solution of 10 mg / mL tetrabutylammonium iodide for 60 seconds to complete the ligand exchange between the solid and liquid phases; use spin coating technology to spin the liquid away from the sample at a speed of 3000 rpm.
[0105] 7) Cover the sample with methanol solution and spin-coate the sample at 3000 rpm; repeat step 8) twice to wash away oleic acid and excess tetrabutylammonium iodide.
[0106] 8) Repeat steps 5) through 7) once.
[0107] 9) The sample obtained in step 8) is annealed at 100°C for 10 minutes to obtain a device based solely on solid-phase coordination exchange.
[0108] Figure 6 The typical dark-state current-voltage curves and near-infrared light irradiation current-voltage curves of the bilayer heterojunction device based on solid-state ligand exchange technology show a significant difference in photocurrent compared to the three-layer heterojunction device designed in this invention.
[0109] Figure 7 The curves showing the specific detectivity and photoresponsivity of a bilayer heterojunction device based on solid-state ligand exchange technology as a function of incident light power are shown. Compared with the three-layer heterojunction device designed in this invention, the specific detectivity and photoresponsivity are significantly different.
[0110] Comparative Example 2:
[0111] 1) Transfer 10 mL of octadecene, 1.5 mL of oleic acid, and 0.446 g of yellow lead oxide to the reaction system. Using a Schlenk linear synthesis system, evacuate the reaction system to a vacuum and stir. After the reaction system is free of bubbles, heat to 95°C until the yellow lead oxide is completely dissolved and the octadecene solution of yellow lead oxide becomes clear and transparent. This process takes approximately 2 hours or more. Clean the reaction system by purging nitrogen gas and then evacuating it to completely isolate it from water and oxygen. After the reaction system reaches 120°C, quickly inject 10 mL of an octadecene solution containing 210 μL of hexamethyldisilazane. Immediately cool the reaction system to room temperature in a cold water bath.
[0112] 2) Add sufficient methanol (approximately 10 mL) to the black solution obtained in step 1) until it separates into layers, and remove the supernatant containing oleic acid. Add excess acetone (approximately 100 mL) to the lower layer of black solution containing quantum dots until the quantum dots settle, and centrifuge to remove the supernatant. Add a small amount of toluene (approximately 1 mL) to dissolve the quantum dots. Repeat the above process three times to wash the quantum dots and remove excess oleic acid ligands. Vacuum dry to obtain oleic acid-terminated lead sulfide quantum dot powder.
[0113] 3) Dissolve the small-sized quantum dot powder obtained in step 2) in n-hexane at a concentration of 10 mg / mL, and mix it with an equal volume of an N,N-dimethylformamide solution of lead iodide and ammonium acetate. The concentration of lead iodide is 0.1 mol / L, and the concentration of ammonium acetate is 0.04 mol / L. Stir the mixture vigorously until it separates into layers, and remove the supernatant. Wash the black quantum dot solution by adding and removing n-hexane. Repeat this washing step three times. Add 10 mL of toluene and centrifuge to allow the quantum dots to settle. Remove the supernatant and vacuum dry for ten minutes to obtain iodine-terminated quantum dot powder. This step is the liquid-phase ligand exchange process.
[0114] 4) A clear glass substrate was selected, and an amorphous indium gallium zinc oxide transparent thin film was deposited using radio frequency magnetron sputtering technology. During the radio frequency magnetron sputtering process, the working pressure was 0.37 Pa, the power was 60 W, and the time was 5 minutes. After sputtering, the sample was annealed on a 400℃ hot plate for 1 hour. Patterning was then completed using a mask and a thermal evaporation coating machine. The metal used for thermal evaporation was aluminum.
[0115] 5) Dissolve the iodine-terminated quantum dots obtained in step 3) at a concentration of 50 mg / mL in a mixed solution of butylamine, pentamine, and hexylamine at a volume ratio of 10:3:2, filter, and obtain iodine-terminated lead sulfide quantum dot ink. Drop this ink onto the sample obtained in step 10), and spin coat it at 2500 rpm for 60 seconds to form a film, thus obtaining a device based solely on liquid-phase ligand exchange.
[0116] Figure 8 The transient response curves of the device based solely on liquid-phase ligand exchange show that the rise time is 51.3 milliseconds and the fall time is 25.8 milliseconds, which is significantly different from the three-layer heterojunction device designed in this invention.
[0117] Figure 9 The curves showing the specific detectivity and photoresponsivity of a device based solely on liquid-phase ligand exchange as a function of incident light power reveal that the device exhibits a specific detectivity exceeding 10. 13 Jones's specific detectivity and ampere-per-watt optical responsivity.
[0118] Example 2:
[0119] 1) Transfer 10 mL of octadecene, 1.5 mL of oleic acid, and 0.446 g of yellow lead oxide to the reaction system. Using a Schlenk linear synthesis system, evacuate the reaction system to a vacuum and stir. After the reaction system is free of bubbles, heat to 95°C until the yellow lead oxide is completely dissolved and the octadecene solution of yellow lead oxide becomes clear and transparent. This process takes approximately 2 hours or more. Clean the reaction system by purging nitrogen gas and then evacuating it to completely isolate it from water and oxygen. After the reaction system reaches 120°C, quickly inject 10 mL of an octadecene solution containing 210 μL of hexamethyldisilazane. Immediately cool the reaction system to room temperature in a cold water bath.
[0120] 2) Add sufficient methanol (approximately 10 mL) to the black solution obtained in step 1) until it separates into layers, and remove the supernatant containing oleic acid. Add excess acetone (approximately 100 mL) to the lower layer of black solution containing quantum dots until the quantum dots settle, and centrifuge to remove the supernatant. Add a small amount of toluene (approximately 1 mL) to dissolve the quantum dots. Repeat the above process three times to wash the quantum dots and remove excess oleic acid ligands. Vacuum dry to obtain oleic acid-terminated lead sulfide quantum dot powder.
[0121] 3) Dissolve the small-sized quantum dot powder obtained in step 2) in n-hexane at a concentration of 10 mg / mL, and mix it with an equal volume of an N,N-dimethylformamide solution of lead iodide and ammonium acetate. The concentration of lead iodide is 0.1 mol / L, and the concentration of ammonium acetate is 0.04 mol / L. Stir the mixture vigorously until it separates into layers, and remove the supernatant. Wash the black quantum dot solution by adding and removing n-hexane. Repeat this washing step three times. Add 10 mL of toluene and centrifuge to allow the quantum dots to settle. Remove the supernatant and vacuum dry for ten minutes to obtain iodine-terminated quantum dot powder. This step is the liquid-phase ligand exchange process.
[0122] 4) A flexible plastic substrate was selected, and an amorphous indium gallium zinc oxide transparent thin film was deposited using radio frequency magnetron sputtering technology. During the radio frequency magnetron sputtering process, the working pressure was 0.37 Pa, the power was 60 W, and the time was 5 minutes. After sputtering, the sample was annealed on a 400℃ hot plate for 1 hour. Patterning was then completed using a mask and a thermal evaporation coating machine. The metal used for thermal evaporation was aluminum.
[0123] 5) Dissolve oleic acid-terminated lead sulfide quantum dots in n-octane solution at a concentration of 5 mg / mL to obtain oleic acid-terminated quantum dot ink.
[0124] 6) Using spin coating technology, the oleic acid-terminated quantum dot ink is spin-coated onto the substrate at a speed of 3000 rpm for 20 seconds.
[0125] 7) Then cover the sample with a methanol solution of 10 mg / mL tetrabutylammonium iodide for 60 seconds to complete the ligand exchange between the solid and liquid phases; use spin coating technology to spin the liquid away from the sample at a speed of 3000 rpm.
[0126] 8) Cover the sample with methanol solution and spin-coate the sample at 3000 rpm; repeat step 8) twice to wash away oleic acid and excess tetrabutylammonium iodide.
[0127] 9) Repeat steps 6) through 8) three times.
[0128] 10) The sample obtained in step 9) is annealed at 100°C for 10 minutes.
[0129] 11) Dissolve the iodine-terminated quantum dots obtained in step 3) at a concentration of 200 mg / mL in a mixed solution of butylamine, pentamine, and hexylamine at a volume ratio of 10:3:2, filter, and obtain iodine-terminated lead sulfide quantum dot ink. Drop-coat this ink onto the sample obtained in step 10), and spin-coat it at 2500 rpm for 60 seconds to obtain a three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector.
[0130] Example 3:
[0131] 1) Transfer 10 mL of octadecene, 1.5 mL of oleic acid, and 0.446 g of yellow lead oxide to the reaction system. Using a Schlenk linear synthesis system, evacuate the reaction system to a vacuum and stir. After the reaction system is free of bubbles, heat to 95°C until the yellow lead oxide is completely dissolved and the octadecene solution of yellow lead oxide becomes clear and transparent. This process takes approximately 2 hours or more. Clean the reaction system by purging nitrogen gas and then evacuating it to completely isolate it from water and oxygen. After the reaction system reaches 120°C, quickly inject 10 mL of an octadecene solution containing 210 μL of hexamethyldisilazane. Immediately cool the reaction system to room temperature in a cold water bath.
[0132] 2) Add sufficient methanol (approximately 10 mL) to the black solution obtained in step 1) until it separates into layers, and remove the supernatant containing oleic acid. Add excess acetone (approximately 100 mL) to the lower layer of black solution containing quantum dots until the quantum dots settle, and centrifuge to remove the supernatant. Add a small amount of toluene (approximately 1 mL) to dissolve the quantum dots. Repeat the above process three times to wash the quantum dots and remove excess oleic acid ligands. Vacuum dry to obtain oleic acid-terminated lead sulfide quantum dot powder.
[0133] 3) Dissolve the small-sized quantum dot powder obtained in step 2) in n-hexane at a concentration of 10 mg / mL, and mix it with an equal volume of an N,N-dimethylformamide solution of lead iodide and ammonium acetate. The concentration of lead iodide is 0.1 mol / L, and the concentration of ammonium acetate is 0.04 mol / L. Stir the mixture vigorously until it separates into layers, and remove the supernatant. Wash the black quantum dot solution by adding and removing n-hexane. Repeat this washing step three times. Add 10 mL of toluene and centrifuge to allow the quantum dots to settle. Remove the supernatant and vacuum dry for ten minutes to obtain iodine-terminated quantum dot powder. This step is the liquid-phase ligand exchange process.
[0134] 4) A paper substrate was selected, and an amorphous indium gallium zinc oxide transparent thin film was deposited using radio frequency magnetron sputtering technology. During the radio frequency magnetron sputtering process, the working pressure was 0.37 Pa, the power was 60 W, and the time was 5 minutes. After sputtering, the sample was annealed on a 400℃ hot plate for 1 hour. Patterning was then completed using a mask and a thermal evaporation coating machine. The metal used for thermal evaporation was aluminum.
[0135] 5) Dissolve oleic acid-terminated lead sulfide quantum dots in n-octane solution at a concentration of 20 mg / mL to obtain oleic acid-terminated quantum dot ink.
[0136] 6) Using spin coating technology, the oleic acid-terminated quantum dot ink is spin-coated onto the substrate at a speed of 3000 rpm for 20 seconds.
[0137] 7) Then cover the sample with a methanol solution of 10 mg / mL tetrabutylammonium iodide for 60 seconds to complete the ligand exchange between the solid and liquid phases; use spin coating technology to spin the liquid away from the sample at a speed of 3000 rpm.
[0138] 8) Cover the sample with methanol solution and spin-coate the sample at 3000 rpm; repeat step 8) twice to wash away oleic acid and excess tetrabutylammonium iodide.
[0139] 9) Repeat steps 6) through 8) twice.
[0140] 10) The sample obtained in step 9) is annealed at 100°C for 10 minutes.
[0141] 11) Dissolve the iodine-terminated quantum dots obtained in step 3) at a concentration of 100 mg / mL in a mixed solution of butylamine, pentamine, and hexylamine at a volume ratio of 10:3:2, filter, and obtain iodine-terminated lead sulfide quantum dot ink. Drop-coat this ink onto the sample obtained in step 10), and spin-coat it at 2500 rpm for 60 seconds to obtain a three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector.
Claims
1. A three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector, characterized in that: From bottom to top, the layers are: substrate, amorphous indium gallium zinc oxide thin film prepared by radio frequency magnetron sputtering, patterned aluminum electrode, iodine-terminated lead sulfide quantum dot film (PbS-TABI) prepared by solid-phase ligand exchange process, and iodine-terminated lead sulfide quantum dot film (PbS-I) prepared by liquid-phase ligand exchange process. The thickness of the iodine-terminated lead sulfide quantum dot film (PbS-TABI) prepared by solid-phase ligand exchange process is 10-20 nm. The thickness of the iodine-terminated lead sulfide quantum dot film (PbS-I) prepared by liquid-phase ligand exchange process is 30-300 nm.
2. The three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector as described in claim 1, characterized in that: The total thickness of iodine-terminated lead sulfide quantum dot films (PbS-TABI) prepared by solid-phase ligand exchange process and iodine-terminated lead sulfide quantum dot films (PbS-I) prepared by liquid-phase ligand exchange process is 40-320 nm.
3. The three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector as described in claim 1 or 2, characterized in that: The amorphous indium gallium zinc oxide target used for the preparation of amorphous indium gallium zinc oxide thin films has an indium, gallium, and zinc element ratio of 1:1:1, a working pressure of 0.37 Pa, a power of 60 W, and a sputtering time of 5 minutes.
4. The three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector as described in claim 3, characterized in that: The substrate is a white glass substrate, a flexible plastic substrate, or a paper substrate.
5. A method for preparing a three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector as described in claim 4, characterized in that... Includes the following steps: Step 1: An amorphous indium gallium zinc oxide thin film is deposited on a clean and dry substrate using an RF magnetron sputtering process; after annealing, the thin film is used to pattern aluminum electrodes using a mask and thermal evaporation deposition technology. Step 2: Using spin coating technology, a thin film of iodine-terminated lead sulfide quantum dots is deposited on the sample obtained in Step 1 using a solid-phase ligand exchange process. Step 3: Using spin coating technology, iodine-terminated lead sulfide quantum dot ink prepared by liquid phase ligand exchange process is deposited on the sample obtained in step 2 to obtain a three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector.
6. The method for fabricating the three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector as described in claim 5, characterized in that... Step 2 specifically involves: Step 2.1: Dissolve 2 mmol of lead oxide in a mixture of 10 mL of octadecene and 1.5 mL of oleic acid, and evacuate the mixture to a vacuum using a Schlenk linear reaction system. Gradually raise the temperature to 95 °C and maintain this temperature until the turbid lead oxide solution transforms into a clear lead precursor solution. Use an inert gas to repeatedly wash the lead precursor solution with an inert gas using a Schlenk linear reaction system to ensure it is dry and oxygen-free. In an inert gas environment, raise the temperature of the lead precursor solution to 120 °C, and rapidly inject 10 mL of a 0.2 mol / L solution of hexamethyldisilazane in octadecene into the reaction system. Then immediately cool the reaction system to 35 °C using an ice-water bath. Step 2.2: The reaction was completely stopped by injecting 25 mL of acetone into the reaction product of step 2.1, and 20 mL of methanol was added to separate the reaction system into layers and remove the supernatant. Excess acetone was added to precipitate the reaction product, the supernatant was removed, and toluene was added to dissolve the precipitate. The above steps were repeated three times to obtain a solid product, which was dried under vacuum overnight to obtain oleic acid-terminated lead sulfide quantum dots. Step 2.3: Dissolve the oleic acid-terminated lead sulfide quantum dots obtained in step 2.2 in n-octane solution to obtain oleic acid-terminated quantum dot ink with a concentration of 5-50 mg / mL; Step 2.4: Using spin coating technology, spin coat the oleic acid-terminated quantum dot ink onto the substrate at a speed of 3000 rpm for 20 seconds. Step 2.5: Then, cover the sample with a methanol solution of 10 mg / mL tetrabutylammonium iodide for 60 seconds to complete the ligand exchange between the solid and liquid phases; then, using spin coating technology, spin the liquid away from the sample at a speed of 3000 rpm. Step 2.6: Cover the sample with methanol solution and spin-coate the sample at a speed of 3000 rpm. Repeat step 2.6 twice to wash away oleic acid and excess tetrabutylammonium iodide to obtain a PbS-TBAI film. Step 2.7, repeat steps 2.4-2.6 one to three times to obtain a PbS-TBAI film with a thickness of 10-20 nanometers; The samples obtained in steps 2.8 and 2.6 are either not annealed or annealed in air at 50°C to 150°C for 10 minutes.
7. The method for fabricating a three-layer lead sulfide / indium gallium zinc oxide heterojunction photoconductive near-infrared photodetector as described in claim 5, characterized in that... Step 3 specifically involves: Step 3.1: Dissolve 2 mmol of lead oxide in a mixture of 10 mL of octadecene and 1.5 mL of oleic acid, and evacuate the mixture to a vacuum using a Schlenk linear reaction system. Gradually raise the temperature to 95°C and maintain this temperature until the turbid lead oxide solution transforms into a clear lead precursor solution. Use an inert gas to repeatedly wash the lead precursor solution with an inert gas using a Schlenk linear reaction system to ensure it is dry and oxygen-free. In an inert gas environment, raise the temperature of the lead precursor solution to 120°C, and rapidly inject 10 mL of a 0.2 mol / L solution of hexamethyldisilazane in octadecene into the reaction system. Then immediately cool the reaction system to 35°C using an ice-water bath. Step 3.2: The reaction was completely stopped by injecting 25 mL of acetone into the reaction product of step 3.1, and 20 mL of methanol was added to separate the reaction system into layers and remove the supernatant; excess acetone was added to precipitate the reaction product, the supernatant was removed, and toluene was added to dissolve the precipitate; the above steps were repeated three times to obtain a solid product, which was vacuum dried overnight to obtain oleic acid-terminated lead sulfide quantum dots. Step 3.3: Dissolve the oleic acid-terminated lead sulfide quantum dots in n-hexane to obtain a n-hexane solution of oleic acid-terminated quantum dots with a concentration of 10 mg / mL; Step 3.4: Mix the above-mentioned hexane solution of quantum dots with an equal volume of N,N-dimethylformamide solution of lead iodide and ammonium acetate. The concentration of lead iodide was 0.1 mol / L and the concentration of ammonium acetate was 0.04 mol / L. The mixture was stirred vigorously until it separated into layers, and the supernatant was removed. The black quantum dot solution was washed with hexane, 10 mL of toluene was added and centrifuged to allow the quantum dots to precipitate. The supernatant was removed and the mixture was vacuum dried for ten minutes to obtain iodine-terminated quantum dot powder. Step 3.5: Dissolve iodine-capped quantum dot powder at a concentration of 50-200 mg / mL in a mixed solution of butylamine, pentamine, and hexylamine with a volume ratio of 10:3:2, and spin-coat an iodine-capped lead sulfide quantum dot film (PbS-I) at a speed of 2500 rpm for 60 seconds.
